Diagnostic significance of soluble adhesion molecules and costimulatory molecules of immune cells in the patients with ischemic heart disease - A. V. Logatkina (SPb RAACI, 2020)
Ischemic heart disease (IHD) represents significant medical issues, due to high prevalence of the disorder, permanent progressive course, being a leading cause of mortality. With respect to important role of vascular wall inflammation in IHT sipported by the inflammatory macrophages, Т cells and NK cells, one should conclude that their activation markers may play certain role in evaluation of intensity of immune inflammation, and, therefore, they could be used for prediction of health consequences for the patients. Hence, the aim of this study was to assess diagnostic value of soluble co-stimulatory molecules, as well as adhesion molecules in the patients with effort angina and acute coronary syndrome. In the course of controlled clinical study, we have examined 48 patients with IHD, of both genders at the age of 55 to 70 years, as well as 15 healthy persons aged 50 to 70 лет. The main group of IHD patients was divided into 2 subgroups: the 1st subgroup included 25 cases with effort angina, functional class 2-3; the 2nd subgroup consisted of 23 patients admitted to the clinic with acute coronary syndrome with ST elevation on ECG, and GRACE score of 125 to 140 points. The mean age of the observed patients was 68.5±5.0 years old). In the course of the study, serum contents of adhesion molecules (sICAM-1, sVCAM-1, leukocyte (L) and platelet (P) selectins), like as sCD28, sCD40, sCD40L, sCD80, sCD152, sFas, sFasL were measured by means of immunoenzyme technique. The data analysis has shown an increase of sCD152 levels by 77.8% (р = 0.026); sCD40 elevated by 22.2% (р = 0.038), and sVCAM was increased 1.98-fold (р = 0.011) in the effort angina patients. Similarly, we revealed a decrease in L- and P-selectins, respectively, by 51.6% (р = 0.029), and 29.0 % (р = 0.04), as well as decrease of sСD80 by 77.1% (р = 0.026); sCD40L by 30.8% (р = 0.041), sFas by 54.4 (р = 0.038), sFasL на 32.5% (р = 0.043). In acute coronary syndrome, if compared to control group, an increase in sCD152 was found by 61.1% (р = 0.029); sCD40 by 29.6% (р = 0.041); sVCAM-1 was elevated 3.16-fold (р = 0.001), along with decreased concentrations of L-selectin by 71.6% (р = 0.025); P-selectin by на 32.1% (р = 0.043); sCD80 by 76.4% (р = 0.023); sCD28 by 48.1% (р = 0.038); sCD40 by 29.6% (р = 0.046); sCD40L by 28.2% (р = 0.045); sFas by 48.5% (р = 0.041); sFasL by 12.5% (р = 0.05). The patients with acute coronary syndrome, in comparison with effort angina, exhibited a diminished L-selectin expression by 41.3% (р = 0.033); sCD28 by 30.1% (р = 0.036); sFasL by 29.6% (р = 0.041); sFas by 12.5% (р = 0.06), whereas sVCAM-1 levels were increased by 59.0% (р = 0.027). The examined patients with IHD exhibited increased levels of serum sCD152, sCD40 and sVCAM-1, along with decreased expression of L- and P-selectins, sCD80, sCD40L, as well as sFas and sFasL. In presence of acute coronary syndrome, a more pronounced drop in L-selectin, sVCAM-1, sCD28, sFasL and sFas expression like as relative increase of FasL over Fas levels. L-selectin is the most precise marker of acute coronary syndrome, with informativity of 91% and diagnostic threshold of 7.7 ng/mL (95% CI, 78-98%), as well as FasL with informativity of 93% (84-99%) and diagnostic value of 3.1 ng/mL. The detected changes of the markers studied in acute coronary syndrome, in particular, increased FasL levels and diminished CD28 presume a possible pathogenetic relation between development of the IHD exacerbation and imbalance between T-regulatory lymphocytes and Th17 helper cells as well as pronounced apoptosis activation of endotheliocytes in coronary arteria.